Human Potentials Management in Transport - Pupavac, Drago; Zelenika, Ratko; Jurčević, Marinko (Promet - Traffic&Transportation, 2004)
The main goal of this scientific study is to explore the significanceof human potentials management in micro and macrotransport systems, i. e. whether and to what extent do the humanpotentials represent the factor of growth and developmentof transport systems. The facts gathered by this study shouldrepresent quantitative starting points for viewing the specifics oftransport service productions and future movements on thetransport labour market, and the possibilities of informationtechnologies implementation in transport human potentialsmanagement optimisations, all with the aim of producing newand of improving the inherited comparative advantages of theCroatian transport systems.